The Relationship between History of Breastfeeding and Obesity on Elementary School Children (SCRIPTA SCORE Scientific Medical Journal, 2020)
ABSTRACTObesity is a public health concern that its prevalence and intensity on children have been increasing with alarming status. Breastfeeding has been considered as one of protective factors that can prevent childhood obesity. The aim of this study is to discover the relationship between history of breastfeeding and obesity on elementary school children. This is an analytical study with cross sectional design. All children in first and second grade of Namira Islamic Elementary School and their mothers were included as population. Ninety samples were recruited randomly. Data on breastfeeding history were collected by using questionnaire guided interview from the mothers. The BMI-for-age curve CDC 2000 was used to determine obesity status of the children (â‰¥ 95th percentile). Data were analyzed using chi-square test. This study found percentage of children with and without history of breastfeeding consecutively is 92.2% and 7.8%. Prevalence of children with obesity is 12.2% and without obesity is 87.8%. Eight of 83 children with history of breastfeeding (72.7%) were obese, and 3 of 7 children without history of breastfeeding (27.3%) were obese (PR=0.2; 95% CI=0.27-0.752;p